What drives Malaysian m-commerce adoption? An empirical analysis - Wei, Toh Tsu; Marthandan, Govindan; Chong, Alain Yee Loong; Ooi, Keng Boon; Arumugam, Seetharam (Emerald Group Publishing Limited, 2009)
Purpose – This study aims to empirically examine the factors that affect the consumer intention to use (IU) mobile commerce (m-commerce) in Malaysia. The five factors examined in this study are perceived usefulness (PU), perceived ease-of-use (PEOU), social influence (SI), perceived cost and trust. Design/methodology/approach – The study sample consists of 222 respondents with a response rate of 84.09 per cent. Data were analyzed by employing correlation and multiple regression analysis. Findings – The findings revealed that PU, SI, perceived financial cost and trust are positively associated with consumer IU m-commerce in Malaysia. In addition, PEOU and trust were found to have an insignificant effect on consumer IU m-commerce in Malaysia. Research limitations/implications – The generalizability of the findings is limited as the study focuses only on Malaysia. Practical implications – Based on the findings, companies involved in m-commerce should focus on improving the usefulness of the system, trust (i.e. security and privacy protection) and reducing the cost of m-commerce services to improve the adoption of m-commerce. Originality/value – The findingsmade a contribution in terms of allowing us to understand the factors that can contribute to the adoption of mobile commerce.This study successfully extend theTAMmodel in the context of mobile commerce by incorporating one trust-based construct (trust), one behavioural control construct (perceived financial cost) and one subjective norm construct (SI). This extended TAM model provides a greater understanding of user acceptance of mobile commerce in Malaysia.